Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Petani Karet di Desa Hayup Kecamatan Haruai Kabupaten Tabalong - Pamungkas , Dayu Aji; Siregar, Syarituah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This research was conducted to (1) analyze the effect of rubber land area, the number of rubber trees, fertilizer costs, and the number of workers on the income of rubber farmers in Hayup Village, Haruai District, Tabalong Regency. (2) Knowing the most dominant factor influencing the income of rubber farmers in Hayup Village, Haruai District, Tabalong Regency. This research is included in quantitative descriptive research; this study used respondents of 52 rubber farmers in Hayup Village, Haruai District, Tabalong Regency. The data in this study were then processed using multiple linear regression analysis using SPSS version 21 software. This study indicates that together the factors of rubber land area, number of rubber trees, fertilizer costs, and the number of labor force affect the income of rubber farmers in Hayup Village, Haruai District, Tabalong Regency. The most dominant factor influencing the income of rubber farmers in Hayup Village, Haruai District, Tabalong Regency is the fertilizer cost factor.